PH‐Sensitive stimulus‐responsive nanocarriers for targeted delivery of therapeutic agents. (14th January 2016) - Karimi, Mahdi; Eslami, Masoud; Sahandi‐Zangabad, Parham; Mirab, Fereshteh; Farajisafiloo, Negar; Shafaei, Zahra; Ghosh, Deepanjan; Bozorgomid, Mahnaz; Dashkhaneh, Fariba; Hamblin, Michael R.
Abstract : In recent years miscellaneous smart micro/nanosystems that respond to various exogenous/endogenous stimuli including temperature, magnetic/electric field, mechanical force, ultrasound/light irradiation, redox potentials, and biomolecule concentration have been developed for targeted delivery and release of encapsulated therapeutic agents such as drugs, genes, proteins, and metal ions specifically at their required site of action. Owing to physiological differences between malignant and normal cells, or between tumors and normal tissues, pH‐sensitive nanosystems represent promising smart delivery vehicles for transport and delivery of anticancer agents. Furthermore, pH‐sensitive systems possess applications in delivery of metal ions and biomolecules such as proteins, insulin, etc., as well as co‐delivery of cargos, dual pH‐sensitive nanocarriers, dual/multi stimuli‐responsive nanosystems, and even in the search for new solutions for therapy of diseases such as Alzheimer's. In order to design an optimized system, it is necessary to understand the various pH‐responsive micro/nanoparticles and the different mechanisms of pH‐sensitive drug release. This should be accompanied by an assessment of the theoretical and practical challenges in the design and use of these carriers. WIREs Nanomed Nanobiotechnol 2016, 8:696–716. doi: 10.1002/wnan.1389 This article is categorized under: Biology-Inspired Nanomaterials > Lipid-Based Structures Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Therapeutic Approaches and Drug Discovery > Nanomedicine for Infectious Disease